The Cash Budget as Internal Control in Regional Cash Financial Management - Lovita, Erna; Luthfia, Diana; Noormansyah, Irvan (Santoso Academy Network, 2023)
The case study was conducted at the Pandeglang Regency Government, where an urgent need arose when central government transfer funds experienced changes in distribution. The research aims to explain the function of the cash budget in the public sector to achieve efficiency and effectiveness in regional cash management, especially in APBD planning and decision-making regarding the availability of regional government finances. The research method used is qualitative and comparative, namely analyzing certain situations, cases, or groups. The financial management situation of regional cash was analyzed by comparing the before and after implementation of the cash budget as internal control in cash management in Pandeglang Regency. The research results show that the role of the cash budget as an internal control can improve activity planning, cash administration, and activity reporting. The cash budget has also been proven to increase the efficiency and effectiveness of regional cash management, as can be seen from the significant reduction in excess financing. Implementing the cash budget allows the Pandeglang Regency Government to calculate minimum cash and invest the funds to obtain deposits, optimizing the use of funds.